Bone marrow mesenchymal stem cell exosomes-derived microRNA-216a-5p on locomotor performance, neuronal injury, and microglia inflammation in spinal cord injury - Xue, Hao; Ran, Bo; Li, Jie; Wang, Guorui; Chen, Baolin; Mao, Honggang (Frontiers in Cell and Developmental Biology, 2023)
Background: mediates inflammatory responses and neuronal injury to participate in the pathology of spinal cord injury (SCI). This study intended to explore the engagement of bone marrow mesenchymal stem cell exosomes (BMSC-Exo)-derived miR-216a-5p in locomotor performance, neuronal injury, and microglia-mediated inflammation in SCI rats.Methods: Rat BMSC or BMSC-Exo was injected into SCI rats. GW4869 treatment was adopted to suppress the exosome secretion from BMSC. Subsequently, miR-216a-5p-overexpressed BMSC-Exo (BMSC-miR-Exo) or negative-control-overexpressed BMSC-Exo (BMSC-NC-Exo) were injected into SCI rats.: The injection of BMSC or BMSC-Exo enhanced locomotor performance reflected by Basso, Beattie & Bresnahan score (P<0.001), and neuronal viability reflected by NeuN + cells (P<0.01), but attenuated neuronal apoptosis reflected by TUNEL positive rate, cleaved-caspase-3 expression, and B-cell leukemia/lymphoma-2 expression (P<0.05). Additionally, the injection of BMSC or BMSC-Exo suppressed microglia M1 polarization-mediated inflammation reflected by IBA1 + iNOS + cells, tumor necrosis factor-α, interleukin (IL)-1β, and IL-6 (P<0.01). Notably, the effect of BMSC on the above functions was retarded by the GW4869 treatment (most P<0.05). Subsequently, the injection of BMSC-miR-Exo further improved locomotor performance (P<0.05), while inhibiting neuronal apoptosis (P<0.05) and microglia M1 polarization-mediated inflammation (P<0.05) compared to BMSC-NC-Exo. Interestingly, the injection of BMSC-miR-Exo reduced toll-like receptor 4 (TLR4) (P<0.01), myeloid differentiation factor 88 (P<0.05), and nuclear factor kappa B (NF-κB) (P<0.05) expressions versus BMSC-NC-Exo.Conclusion: BMSC-Exo-derived miR-216a-5p enhances functional recovery by attenuating neuronal injury and microglia-mediated inflammation in SCI, which may be attributable to its inhibition of the TLR4/NF-κB pathway.